Exceptionnalisme et impérialisme dans le discours de politique étrangère américain des années Clinton - Frédéric Heurtebize (Revue LISA)
The United States has to a great extent asserted itself as a nation through the victories of its military and, even more so perhaps, through binary oppositions: democratic republic vs. British monarchy, progress vs. barbarity, capitalism vs. Communism, freedom vs. tyranny or, more recently, terror, to name but a few. This article examines the discourse and arguments elaborated throughout the Clinton presidency by politicians and academics to shape and legitimize U.S. foreign policy in peace time. What ideological justifications could underpin the maintenance or strengthening of the U.S. presence worldwide once the Soviet threat had vanished and yet before the dramatic eruption of terrorism in New York and Washington? How to redefine the country’s mission and its national interest? Did America’s exceptionalist rhetoric survive between the end of the Cold War and 9/11? It may be easy to focus the energy and attention of a nation on a clearly identified enemy; but what can be done or said when there is no clearly recognizable target? In other words, are exceptionalism and imperialism intrinsic features of American identity or are they just products of adversity?